Helper T cell IL-2 production is limited by negative feedback and STAT-dependent cytokine signals - Villarino, Alejandro V. (The Rockefeller University Press, 2007)
Although required for many fundamental immune processes, ranging from self-tolerance to pathogen immunity, interleukin (IL)-2 production is transient, and the mechanisms underlying this brevity remain unclear. These studies reveal that helper T cell IL-2 production is limited by a classic negative feedback loop that functions autonomously or in collaboration with other common γ chain (IL-4 and IL-7) and IL-6/IL-12 family cytokines (IL-12 and IL-27). Consistent with this model for cytokine-dependent regulation, they also demonstrate that the inhibitory effect can be mediated by several signal transducer and activator of transcription (STAT) family transcription factors, namely STAT5, STAT4, and STAT6. Collectively, these findings establish that IL-2 production is limited by a network of autocrine and paracrine signals that are readily available during acute inflammatory responses and, thus, provide a cellular and molecular basis for its transient pattern of expression.